Long-term patterns of abiotic drivers of mosquito activity within summer ranges of Northern Alaska caribou herds (1979–2009) - Bali, Archana; Alexeev, Vladimir A.; White, Robert G.; Russell, Don E.; McGuire, A. David; Kofinas, Gary P. (Rangifer, 2013)
-